1984
DOI: 10.1017/s0022215100146791
|View full text |Cite
|
Sign up to set email alerts
|

Benign intracranial hypertension caused by mastoiditis and lateral sinus obstruction: The value of computerized tomography in diagnosis

Abstract: A case of benign intracranial hypertension occurring in an 11-year-old boy, and due to lateral sinus obstruction, is reported. Computerized tomographic scan was conclusive, revealing a normal ventricular system and no evidence of a neoplastic lesion. Disappearance of the mastoid air cells and disruption of the trabecular pattern were also shown on the affected side. The diagnosis was confirmed at operation, and the course was favourable. In accordance with other studies cited, our findings suggest that patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Elevated intracranial pressure may be associated with various conditions, including obesity, autoimmune diseases such as systemic lupus erythematosus, use of certain medications, vitamin deficiencies, vitamin excesses, and bacterial infections, 9,10 including mastoiditis 11 and sinusitis. 12 There are also rare cases of elevated pressure and viral infections such as hepatitis A, measles, and varicella zoster virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated intracranial pressure may be associated with various conditions, including obesity, autoimmune diseases such as systemic lupus erythematosus, use of certain medications, vitamin deficiencies, vitamin excesses, and bacterial infections, 9,10 including mastoiditis 11 and sinusitis. 12 There are also rare cases of elevated pressure and viral infections such as hepatitis A, measles, and varicella zoster virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism of raised intracranial pressure is still unclear (O'Connor and Moffat, 1978) and more sinister pathologies such as brain abscesses and intracranial tumours must be excluded. It is in this respect that computerized tomographic scanning is most helpful (Sch0nsted-Madsen et al, 1984). Symonds (1931) first used the term 'otitic hydrocephalus' to describe the well-known clinical picture of raised intracranial pressure complicating otitis media and with a normal cerebrospinal fluid.…”
Section: Discussionmentioning
confidence: 99%
“…In 1984, Schonsted-Madsen et al reported a case of an 11-year-old patient who had intracranial hypertension secondary to a 'partly compressed and partly thrombosed' sigmoid sinus. 1 That patient did not undergo surgical decompression of the sigmoid sinus until two weeks after he developed bilateral VIth nerve palsies and papilloedema; fortunately, he still made a full recovery. Our patient had surgical decompression of his sigmoid sinus two days after he developed a VIth nerve palsy and papilloedema.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first reported case of intracranial hypertension due to an epidural abscess causing sigmoid sinus compression without thrombosis. In 1984, Schonsted-Madsen et al reported a case of an 11-year-old patient who had intracranial hypertension secondary to a ‘partly compressed and partly thrombosed’ sigmoid sinus 1 . That patient did not undergo surgical decompression of the sigmoid sinus until two weeks after he developed bilateral VIth nerve palsies and papilloedema; fortunately, he still made a full recovery.…”
Section: Discussionmentioning
confidence: 99%